Early detection of kidney problems through voltammetry, potentiometry, amperometry, and impedance electrochemical techniques: A comprehensive review - Nur Ashakirin Binti Mohd Nashruddin S.; Hani Mohamed Salleh F.; Ayunni Mohd Raub A. (Elsevier B.V., 2025)
In the context of biomarker mechanisms, this paper provides an overview of electrochemical energy, which is the conversion of chemical energy into electrical energy or vice versa via electrochemical processes. It also includes a comparative examination at the basic chemical level of renal function. Furthermore, it is possible to differentiate between the conventional and current systems using the process detection method. By preventing the need for severe treatments like dialysis or renal replacement therapy, new techniques for early kidney failure diagnosis can prevent additional kidney damage and, thus, lower the early detection costs associated with kidney transplantation. In this instance, the benefits of electrochemical approaches for detection and improvement have been emphasized, namely through the use of the recently developed, low-cost, small-scale Screen-Printed Electrode (SPE). ? 2024 Elsevier Ltd